A Static Fracturing Technology to Enhance the Permeability of Coalbed: Mechanical Study - Long Wang; Baohua Guo; Zhaofeng Wang (Advances in Civil Engineering)
Low permeability of coalbed has always been a main bottleneck impeding the safety production of coal mines and the high-efficient gas recovery. A static fracturing technology, relied on hydraulic-driving modules to expand outwards for producing artificial fissures in coalbed, is proposed here for coalbed reservoir stimulation. The mechanical model of borehole fracturing is established to clarify the associated mechanisms for fracturing stimulation based on the elastic-plastic mechanics. The numerical results indicate when the fracturing load is over twice as much as in situ stress, the concentration of hoop stress around borehole would be released and the range of fracturing-induced fissures gradually extends with the rising load. While the lateral stress coefficient of strata rising from 1 to 3, the stress distribution around borehole evolves from a ring to a saddle shape, resulting in the horizontal extension of fissures in the early stage. According to underground monitoring, a significant improvement of coalbed permeability up to 5 times has been achieved in 16031 tailgate, in Guhanshan coalmine, China.